(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2023)
Cashmirins A (1) and B (2), new prenylated coumarins, have been isolated from the EtOAc- soluble fraction of the whole plant of Sorbus cashmiriana Hedlung, Monog. along with seselin (3), scopoletin (4), 3-hydroxyxanthyletin (5) and luteolin (6), reported for the first time from this species. Their structures were elucidated by spectroscopic techniques including MS, 1D and 2D NMR spectroscopy. Both new compounds 1 and 2 were investigated for biological activities and showed significant antifungal and urease inhibitory activities. Compounds 1 and 2 exhibited significant activity against Aspergillus flavus, Macrophomina phaseolina, Trichophyton simii, Trichophyton schoenleinii, and Pseudallescheria boydri. Both compounds also exhibited significant inhibitory activity against Jack bean urease with IC50 values of 28.2±0.12 µM and 30.3±0.18 µM, respectively compared to thiourea used as positive control.